Bacteria-derived fluorescent carbon dots for microbial live/dead differentiation. Issue 6 (22nd November 2016) - Hua, Xian-Wu; Bao, Yan-Wen; Wang, Hong-Yin; Chen, Zhan; Wu, Fu-Gen
Abstract : Hydrothermal treatment of bacterial cells leads to the formation of fluorescent carbon dots that can effectively and accurately differentiate live microorganisms from dead ones. Abstract : Microbial viability assessment plays a key role in many areas such as pathogen detection, infectious disease treatment and antimicrobial drug development. Many conventional viability dyes (such as propidium iodide, PI) used for differentiating live/dead microbes suffer from notable cytotoxicity, poor photostability and are of high cost. Thus their applications for accurate microbial viability determination are limited. Herein, for the first time we report the successful synthesis of fluorescent carbon dots (CDs) from bacteria via one-step hydrothermal carbonization. Benefiting from their highly negative surface charge (the zeta potential is as high as around −42 mV) and suitable size, the CDs can selectively stain dead microbial cells (bacteria and fungi) but not live ones. Importantly, compared to the widely used commercial dye PI, the developed CDs possess many great advantages including low cytotoxicity, multicolor imaging ability, excellent photostability and high selectivity. Moreover, because the synthetic method is simple, inexpensive and eco-friendly, this type of CD is suitable for large-scale production, making it an excellent candidate for microbial live/dead differentiation and viability assessment. The present work explores the feasibility of using bacteria to fabricate novel CDs and broadens the applications of CDs for biomedical applications.